Right hospital, right patients: Penetrating injury patients treated at high-volume penetrating trauma centers have lower mortality. Issue 6 (June 2019) - Fu, Chih-Yuan; Bajani, Francesco; Tatebe, Leah; Butler, Caroline; Starr, Frederic; Dennis, Andrew; Kaminsky, Matthew; Messer, Thomas; Schlanser, Victoria; Kramer, Kristina; Poulakidas, Stathis; Cheng, Chi-Tung; et al.
Abstract : BACKGROUND: The recognition of the relationship between volume and outcomes led to the regionalization of trauma care. The relationship between trauma mechanism-subtype and outcomes has yet to be explored. We hypothesized that trauma centers with a high volume of penetrating trauma patients might be associated with a higher survival rate for penetrating trauma patients. METHODS: A retrospective cohort analysis of penetrating trauma patients presenting between 2011 and 2015 was conducted using the National Trauma Database and the trauma registry at the Stroger Cook County Hospital. Linear regression was used to determine the relationship between mortality and the annual volume of penetrating trauma seen by the treating hospital. RESULTS: Nationally, penetrating injuries account for 9.5% of the trauma cases treated. Patients treated within the top quartile penetrating-volume hospitals (≥167 penetrating cases per annum) are more severely injured (Injury Severity Score: 8.9 vs. 7.7) than those treated at the lowest quartile penetrating volume centers (<36.6 patients per annum). There was a lower mortality rate at institutions that treated high numbers of penetrating trauma patients per annum. A penetrating trauma mortality risk adjustment model showed that the volume of penetrating trauma patients was an independent factor associated with survival rate. CONCLUSION: Trauma centers with high penetrating trauma patient volumes are associated with improved survival of these patients. This association with improved survival does not hold true for the total trauma volume at a center but is specific to the volume of the penetrating trauma subtype. LEVEL OF EVIDENCE: Prognostic/Epidemiology Study, Level-III; Therapeutic/Care Management, Level IV.